2018
DOI: 10.1016/j.ejmech.2017.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in microtubule-stabilizing agents

Abstract: Highly dynamic mitotic spindle microtubules are superb therapeutic targets for a group of chemically diverse and clinically successful anticancer drugs. Microtubule-targeted drugs disrupt microtubule dynamics in distinct ways, and they are primarily classified into two groups: microtubule destabilizing agents (MDAs), such as vinblastine, colchicine, and combretastatin-A4, and microtubule stabilizing agents (MSAs), such as paclitaxel and epothilones. Systematic discovery and development of new MSAs have been ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 202 publications
3
74
0
1
Order By: Relevance
“…Although many chemically diverse synthetic tubulin inhibitors have been synthesized, there is still a need to identify novel small molecules that target microtubules [24][25][26][27][28]. Among such compounds, thiophene [29][30][31][32][33][34] and fused thiophenes such as benzo [b]thiophenes [35][36][37][38][39][40], thieno [3,2-d]pyrimidines [41][42][43], and thieno [2,3-b]pyridines [44] were present as molecular skeletons in a significant number of synthetic inhibitors of microtubule polymerization, but there are limited examples of small molecules showing interesting activities in inhibiting both microtubule assembly and cell proliferation based on the 4,5,6,7-tetrahydrothieno [2,3-c]pyridine molecular skeleton as the core structure.…”
mentioning
confidence: 99%
“…Although many chemically diverse synthetic tubulin inhibitors have been synthesized, there is still a need to identify novel small molecules that target microtubules [24][25][26][27][28]. Among such compounds, thiophene [29][30][31][32][33][34] and fused thiophenes such as benzo [b]thiophenes [35][36][37][38][39][40], thieno [3,2-d]pyrimidines [41][42][43], and thieno [2,3-b]pyridines [44] were present as molecular skeletons in a significant number of synthetic inhibitors of microtubule polymerization, but there are limited examples of small molecules showing interesting activities in inhibiting both microtubule assembly and cell proliferation based on the 4,5,6,7-tetrahydrothieno [2,3-c]pyridine molecular skeleton as the core structure.…”
mentioning
confidence: 99%
“…These doses were at least 10 times higher than the concentrations used in this study for EpoB. In addition, compared with taxol, EpoB has shown to have higher solubility, smaller molecular size, and ability to easily pass through the BBB (Chao et al, 2015; Cao et al, 2018). Another study showed adding 1–3 nM of taxol can increase the neurite growth of mature rat retinal ganglion cells ~40 µm and 10 nM showed a significant reduction of neurite length (Sengottuvel et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Microtubules, which constitute the cytoskeleton, are major cellular mechanical structures and mediate the cell cycle, cell mechanics, and subcellular transport . These structures resemble hollow cylindrical tubes composed of 13 linear protofilaments built from α‐ and β‐tubulins . PPIs between α‐ and β‐tubulins mediate the dynamics of microtubules (MTs), which are essential to their functions and are involved in oncogenesis .…”
Section: Allosteric Modulators To Stabilize Ppismentioning
confidence: 99%
“…194 These structures resemble hollow cylindrical tubes composed of 13 linear protofilaments built from αand β-tubulins. 11,195,196 PPIs between αand β-tubulins mediate the dynamics of microtubules (MTs), which are essential to their functions and are involved in oncogenesis. [197][198][199] Therefore, microtubule-stabilizing agents (MSAs), which stabilize intertubulin PPIs, halt abnormal cell cycles and induce apoptosis, 198,200,201 have become a dynamic field of cancer therapeutics and are now frequently used as anticancer drugs.…”
Section: Microtubulesmentioning
confidence: 99%